Ethnic challenges beyond borders : Chinese and Russian perspectives of the Central Asian conundrum - Azizian, Rouben; Zhang, Yongjin, editor (Hampshire : Macmillan Press, 1998)
In association with St. Anthony's College, Oxford
Keywords: Asia, Central -- Economic conditions; Asia, Central -- Foreign relations -- 1991-.; Asia, Central -- Politics and government -- 1991-.; Asia, Central -- Strategic aspects; Ethnicity -- Asia, Central; sia, Central -- Foreign relations -- China